The Case Study of Life Cycle Perspective in Ready-mix Industry - Yosephine Dwi Martina Widowati (Indonesian Journal of Life Cycle Assessment and Sustainability, 2017)
ASEAN Economic Community (AEC) is a global commitment and has been started since December 2015. Globalization encourages countries to develop their own environment voices as environment has been also a global issue. Infrastructure is one of the key developments. Construction, which is an important part of infrastructure development depends heavily on the concrete industry. Ready-mix concrete  is preferred material for construction because it  has a good quality, ready to use, and cheaper. The thirty mega construction projects which have to be completed in 2019 will push ready-mix concrete industries to grow fast. This grow will undoubtedly have an impact on the environment.The  purpose of this study is to observe the environmental impact of ready-mix concrete industry. This will cover an observation of life cycle perspective implementation, identification of the main potential environmental impacts and risks,  identification of control and influence, and  identification of the potential improvement opportunities. This study will hopefully contribute to the improvement of environmental awareness and stimulate more exhaustive research or study about environmental impact in Ready-mix concrete industry in the future. The method of this qualitative study is site observation and indirect investigation which included 15 plants at multiple locations. This study also addressed idea(s) around the understanding of life cycle perspective approach as described in the newest version of ISO 14001-2015 and ISO 14004-2016.